2016
DOI: 10.1002/mmce.20992
|View full text |Cite
|
Sign up to set email alerts
|

Interconnect reliability analysis of ULSI using automated model generation algorithm

Abstract: Fast interconnect reliability analysis is needed with the rapid development of ULSI (Ultra Large Scale Integration). Therefore, we aims to use the automated model generation (AMG) algorithm to analyze the ULSI reliability of metal interconnects. This is the first time to use the AMG algorithm in the field of IC reliability analysis. The AMG algorithm can achieve data generation automatically, determination of data distribution, adaptation of model structure, model training and testing. Using AMG algorithm in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Step 3) Each processor reads the corresponding file, i.e., the ith processor reads the file containing N l,i training data, then computes E k train,i and ∂E k train,i ∂w using (16) and (17).…”
Section: Parallel Ann Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Step 3) Each processor reads the corresponding file, i.e., the ith processor reads the file containing N l,i training data, then computes E k train,i and ∂E k train,i ∂w using (16) and (17).…”
Section: Parallel Ann Trainingmentioning
confidence: 99%
“…The computationally intensive and time-consuming ANN training during adaptive sampling process in [14] is replaced by simple and efficient interpolation computation, thus making AMG faster than that in [14]. This modified AMG algorithm [15] has been applied in microwave power amplifier modeling [16] and interconnect reliability analysis [17]. However, the existing AMG with interpolation approaches in [15] is based on a sequential computation mechanism, involving sequential interpolation calculation for all subregions during adaptive data sampling, sequential data generation by repetitively driving detailed EM/physics/circuit simulators, and batch ANN model training through iterative training stages.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that failure rate caused by EM is extremely high after 0.18um technology node in Al [17]. Nowadays, EM can be predicted by combing the FEA and ANN techniques for ICs [18], [19]. In addition, the introduction of new materials and processing schemes leads to even more challenges in guaranteeing interconnect robustness.…”
Section: Volume 8 Number 3 July 2019mentioning
confidence: 99%